The Influence of Islamic Work Ethics on Organizational Commitment and Performance of Halal Restaurant Employees - Muhajir, Muhammad Nur Alam; Erwin, Erwin; Hamida, Ambas; Sukran, Sukran (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 1, Februari 2023 (pp.1-186)DO - 10.24843/JEKT.2023.v16.i01.p06, 2023)
This study aims to determine the application of Islamic work ethics by employees who work in halal-certified restaurants in DKI Jakarta on organizational commitment and performance. This study uses the Partial Least Square (PLS) analysis test with 161 samples from employees of halal restaurants in DKI Jakarta. From the research conducted, the researcher found that Islamic work ethic was statistically proven to have a positive effect on affective commitment, continuance commitment, and normative commitment. Islamic work ethic is also statistically proven to have a positive effect on employee performance. Affective commitment and continuance commitment are not proven to have an effect on employee performance (job performance). The normative commitment variable has been shown to have a positive effect on employee performance (job performance).